2010
DOI: 10.1002/fld.2422
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Lagrangian–Eulerian computation of propagation and rupture of a liquid plug in a tube

Abstract: SUMMARYLiquid plug propagation and rupture occurring in lung airways can have a detrimental effect on epithelial cells. In this study, a numerical simulation of a liquid plug in an infinite tube is conducted using an Eulerian-Lagrangian approach and the continuous interface method. A reconstruction scheme is developed to allow topological changes during plug rupture by altering the connectivity information about the interface mesh. Results prior to the rupture are in reasonable agreement with the study of Fuji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 34 publications
5
28
0
Order By: Relevance
“…The sources of experimental uncertainties are (i) the response time of the MFCS controller (about 100 ms ), (ii) the uncertainty of 7.5 µbar on the pressure imposed by the MFCS controller and (iii) the variations of the initial plug length l (about 5%). The present theory is also in qualitative agreement with the numerical simulations of Hassan et al 42 , who found a transition between acceleration and deceleration dynamics for h p = 0.09 − 0.10 andl = 1 at ∆P c = 0.5, and forh p = 0.05, 6 Phase diagram of the dynamics of a 3 µL (length l =3.80 mm) liquid plug pushed at different pressure head ∆P inside tubes covered with prewetting films of different thicknessesh p . Blue empty points correspond to the acceleration regime and green filled points to the deceleration regime.…”
Section: Plug Dynamics At Constant Pressuresupporting
confidence: 90%
“…The sources of experimental uncertainties are (i) the response time of the MFCS controller (about 100 ms ), (ii) the uncertainty of 7.5 µbar on the pressure imposed by the MFCS controller and (iii) the variations of the initial plug length l (about 5%). The present theory is also in qualitative agreement with the numerical simulations of Hassan et al 42 , who found a transition between acceleration and deceleration dynamics for h p = 0.09 − 0.10 andl = 1 at ∆P c = 0.5, and forh p = 0.05, 6 Phase diagram of the dynamics of a 3 µL (length l =3.80 mm) liquid plug pushed at different pressure head ∆P inside tubes covered with prewetting films of different thicknessesh p . Blue empty points correspond to the acceleration regime and green filled points to the deceleration regime.…”
Section: Plug Dynamics At Constant Pressuresupporting
confidence: 90%
“…The fluid viscosity, μ, and surface tension, σ, combine with U p and a to create the trailing film of thickness h. This deposited film reduces the plug volume, so less is delivered distally. If the remaining local plug volume in any airway is fully deposited into the trailing film, the plug ruptures, reinstating continuous gas flow, but halting further delivery downstream from that point (30)(31)(32). That reduces overall efficiency as well as homogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…5(a)) means the film would be long at high yield stress, small pressure drop, and long initial plug. The reason is that each of the three conditions results in slow plug motion, and the film is thin and therefore long as the plug moves slowly (Fujioka and Grotberg, 2004;Fujioka et al, 2008;and Hassan et al, 2011). For the plug studied here with initial length no shorter than 0.59a, the film is generally longer than 2a (the channel width).…”
Section: B Plug Deformation and Rupturementioning
confidence: 99%
“…Shear stress and pressure at walls are maximal at the front meniscus of the plug (Fujioka and Grotberg, 2004). Stresses reach their peaks shortly after the rear meniscus catches up with the front meniscus and rupture happens (Hassan et al, 2011). The high shear stress and pressure may cause lethal damage to underlying epithelial cells, especially at the rupture location (Huh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation